Entwicklung eines virtuellen Musikinstruments auf Basis der Impulse Pattern Formulation - Nadja Rutsch (2022)
The Impulse Pattern Formulation by Bader (2013) is a systematic approach for the description of musical instruments. This approach is used as basis for the realisation of a virtual musical instrument. In order to use the IPF as basis of the instrument, its meaning in terms of sound design parameters must be formulated. This is done by looking at sound generation in the violin. The formulated sound design parameters should be controlled by the IPF. For this purpose a program in the development enviroment Max/MSP is built. The program can be used as a virtual musical instrument. An Artificial Neural Network is implemented as part of the instrument, in order to raise its playability. The IPF is able to design overtones, noise components and transients of sound.The virtual musical instrument can be described as real-time capable. It can be used as basis for further developments.